SoloRider: An Autonomous Self-Balancing Electric Bike for Sustainable Urban Mobility - Sujal Patel; Vihaa Shah; Dr. Nilesh Prajapati (International Journal of Electronics Automation, 2026)
Rapid urbanization has intensified challenges such as traffic congestion, parking inefficiency, and environmental degradation. While autonomous vehicle research predominantly focuses on four-wheel platforms, lightweight two-wheelers remain comparatively underexplored. Two-wheelers are a great option for sustainable urban transportation because of their many benefits, including their small size, lower energy consumption, better manoeuvrability, and lesser infrastructure requirements. This paper presents SoloRider, a conceptual autonomous self- balancing electric two-wheeler de- signed for sustainable urban mobility. The proposed framework integrates inverted pendulum-based stabilization, layered sensor fusion, closed-loop control, and intelligent navigation architecture. Analytical modeling establishes the theoretical feasibility of dynamic balance control and autonomous integration within a compact electric mobility platform. The framework uses a variety of sensors, including as positioning modules, ultrasonic sensing, and inertial measurement units, to continually track obstacle proximity, vehicle orientation, and navigation parameters. A prototype implementation is currently under development to validate real-world perfor- mance in future work. For safe and dependable operation, the study emphasises the possibility of combining autonomous navigation algorithms, real-time decision-making, and adaptive control systems. In order to experimentally verify the suggested autonomous two-wheeler platform& balancing performance, navigational accuracy, and practical operating capabilities in further work, a prototype implementation is now being developed under practical conditions.
Keywords: Self-Balancing System; Smart cities; autonomous vehicles; electric mobility; sensor fusion